14-3x=-4(4x+2)-4(-3-3x)

Simple and best practice solution for 14-3x=-4(4x+2)-4(-3-3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14-3x=-4(4x+2)-4(-3-3x) equation:


Simplifying
14 + -3x = -4(4x + 2) + -4(-3 + -3x)

Reorder the terms:
14 + -3x = -4(2 + 4x) + -4(-3 + -3x)
14 + -3x = (2 * -4 + 4x * -4) + -4(-3 + -3x)
14 + -3x = (-8 + -16x) + -4(-3 + -3x)
14 + -3x = -8 + -16x + (-3 * -4 + -3x * -4)
14 + -3x = -8 + -16x + (12 + 12x)

Reorder the terms:
14 + -3x = -8 + 12 + -16x + 12x

Combine like terms: -8 + 12 = 4
14 + -3x = 4 + -16x + 12x

Combine like terms: -16x + 12x = -4x
14 + -3x = 4 + -4x

Solving
14 + -3x = 4 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
14 + -3x + 4x = 4 + -4x + 4x

Combine like terms: -3x + 4x = 1x
14 + 1x = 4 + -4x + 4x

Combine like terms: -4x + 4x = 0
14 + 1x = 4 + 0
14 + 1x = 4

Add '-14' to each side of the equation.
14 + -14 + 1x = 4 + -14

Combine like terms: 14 + -14 = 0
0 + 1x = 4 + -14
1x = 4 + -14

Combine like terms: 4 + -14 = -10
1x = -10

Divide each side by '1'.
x = -10

Simplifying
x = -10

See similar equations:

| y=1.7x-2.7 | | 12.50x+7.25=32.50+5.25x | | 7=(11-n) | | 7+9lnx=88 | | 4a=sb-7 | | 6(m+1)=42 | | -2(x-5)-2x=7-4(x+3) | | 306=w^2+w | | 306=x^2+X | | 100x^2y-81y=0 | | 5(4x-2)+9=2(4x+7) | | 378+3x-4=25.42 | | (X+y)(x-Y)=1000001 | | r-12=5r | | 9X+3x-4=25.42 | | 111t-4.9t^2=0 | | 0.075(x+4000)=0.08x+0.05(1000) | | 6(5+5)= | | 5x-23-5-3x=8 | | Y=9-7(-1) | | x^2+2+2x=x^2+x-1 | | 5x+3=3x-3+2x+6 | | 15x+6+4=-35 | | 2n-8=3n+36 | | log[3](9x-2)+log[3]8=4 | | y=0.6x-2.4 | | 4(6.5-1.25y)+5y=0 | | 2n-9=5n+36 | | 10r+5=43 | | 4(6.5-1.25y)+5y=26 | | 5X-3=3X-4 | | -6.5=3.5+2x |

Equations solver categories